TOPOGRAPHY & CROSS SECTION MEASUREMENT FOR CALCULATING THE COASTAL BORDER - Gede Yasada; Ida Bagus Putu Bintana (Logic : Jurnal Rancang Bangun dan Teknologi, 2018)
The coastal border is a land along of the shoreline, in which its wide is proportional to the shape and physical condition of the beach, at least 100 meters from the high water level towards the land. This research is based on the results of topography and cross section measurement work at Berawa Canggu Beach, Badung Bali, followed by calculation, drawing and reporting. The required data is the existing base data in the planned area in full to find the position of High Water Level in the field which will be used for the reference of the boundary limit for the coastal planning. The results obtained from this research are: the coastal border position is measured from BM W.3 along 55.1712 meters into the land of ownership and the coastal border position is measured from BM W.4 along 50.6926 meters into the land of ownership.